Acute kidney injury and long-term renal function after partial nephrectomy—is there a true association? - Kim, Won Ho; Yoon, Hyun-Kyu; Lee, Ho-Jin (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Acute kidney injury (AKI) is a common complication after partial nephrectomy with its incidence up to 54% (1,2). Nephrectomy-induced chronic renal insufficiency is associated with increased mortality (3) and a new baseline estimated glomerular filtration rate (eGFR) can impact survival after nephrectomy (4,5). As postoperative AKI is now considered to be interconnected with chronic kidney disease (CKD) (6), the AKI after nephrectomy could be also associated with the development of long-term renal functional decline and eventually CKD. However, the potential impact of AKI after partial nephrectomy on long-term renal function has been debated.